2016
DOI: 10.1111/jon.12371
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian Steal Syndrome with or without Arterial Stenosis: A Review

Abstract: The subclavian-vertebral artery steal syndrome (SSS) is the hemodynamic phenomenon of blood flow reversal in the vertebral artery due to significant stenosis or occlusion of the proximal subclavian artery or the innominate artery. Occasionally, SSS is diagnosed in patients not harboring arterial stenosis. With the exception of arterial congenital malformations, the limited case reports of SSS with intact subclavian artery are attributed to dialysis arteriovenous fistulas (AVFs). Interestingly, these cases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…It has been suggested that the term "vascular steal syndrome" be used only when diversion of ow is accompanied by symptoms of de cient circulation and that "steal phenomenon" or "steal effect" be used when the steal is asymptomatic (17). Common arterial steal syndromes include the subclavian artery steal (18), the vertebrobasilar artery steal and the carotid artery steal (19)(20)(21). In our study, two of ve cases of new cerebral infarction were contralateral posterior circulation infarction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the term "vascular steal syndrome" be used only when diversion of ow is accompanied by symptoms of de cient circulation and that "steal phenomenon" or "steal effect" be used when the steal is asymptomatic (17). Common arterial steal syndromes include the subclavian artery steal (18), the vertebrobasilar artery steal and the carotid artery steal (19)(20)(21). In our study, two of ve cases of new cerebral infarction were contralateral posterior circulation infarction.…”
Section: Discussionmentioning
confidence: 99%
“…There have been sporadic reports of reversed vertebral artery flow in patients with upper extremity dialysis access fistulas. Four published reports of subclavian steal phenomena attributed solely to high‐flow dialysis access sites were identified in the literature …”
Section: Discussionmentioning
confidence: 99%
“…A subclavian steal is characterized by retrograde flow through the vertebral artery. The usual cause is a flow‐reducing stenosis or occlusion of the subclavian artery proximal to the origin of the vertebral artery . However, there are sporadic reports in the medical literature in which the retrograde flow through the vertebral artery was associated not with decreased flow but, rather, with increased flow through the subclavian artery, such as caused by a dialysis access fistula …”
mentioning
confidence: 99%
“…The atrial septum defect with right-left shunt can give rise to paradoxical emboli when a clot migrates from the right to the left side of the heart during a Valsalva maneuver. Subclavian-vertebral artery steal syndrome (SSS) is characterized by blood flow reversal in the vertebral artery due to significant stenosis or occlusion of the proximal ipsilateral subclavian artery or the innominate artery [6]. It is often asymptomatic and an incidental finding, but may also result in significant vertebrobasilar ischemia presenting mostly with transient ischemic attacks [6].…”
Section: Discussionmentioning
confidence: 99%
“…Subclavian-vertebral artery steal syndrome (SSS) is characterized by blood flow reversal in the vertebral artery due to significant stenosis or occlusion of the proximal ipsilateral subclavian artery or the innominate artery [6]. It is often asymptomatic and an incidental finding, but may also result in significant vertebrobasilar ischemia presenting mostly with transient ischemic attacks [6]. The role of the total occlusion of the left subclavian artery with subsequent subclavian steal syndrome in the development of the right medulla oblongata infarction is part of discussion in our patient as CTA scan of the brain could only detect diffuse atherosclerosis without any obstruction or stenosis in the carotid or vertebral artery system.…”
Section: Discussionmentioning
confidence: 99%